2021
DOI: 10.1177/02676591211026514
|View full text |Cite
|
Sign up to set email alerts
|

Modular minimally invasive extracorporeal circulation ensures perfusion safety and technical feasibility in cardiac surgery; a systematic review of the literature

Abstract: Introduction: Despite extensive evidence that shows clinical of superiority of MiECC, worldwide penetration remains low due to concerns regarding air handling and volume management in the context of a closed system. The purpose of this study is to thoroughly investigate perfusion safety and technical feasibility of performing all cardiac surgical procedures with modular (hybrid) MiECC, as experienced from the perfusionist’s perspective. Methods: We retrospectively reviewed perfusion charts of consecutive adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Available evidence suggests that almost 95% of cardiac surgery could be performed with a type III MiECC, while conversion to an open CPB circuit is reserved in less than 5% of cases and for a partial procedural time. 8 It should be noted that shed blood management represents an integral component of MiECC. 2 As MiECTiS emphasized in 2016 position paper, no advancement in perfusion technology could substitute for meticulous surgical technique, which remains the cornerstone for achieving an optimal surgical outcome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Available evidence suggests that almost 95% of cardiac surgery could be performed with a type III MiECC, while conversion to an open CPB circuit is reserved in less than 5% of cases and for a partial procedural time. 8 It should be noted that shed blood management represents an integral component of MiECC. 2 As MiECTiS emphasized in 2016 position paper, no advancement in perfusion technology could substitute for meticulous surgical technique, which remains the cornerstone for achieving an optimal surgical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…85 A systematic review of the literature revealed no clinical adverse event in any patient related to MiECC to date. 8 In the light of this evidence, MiECTiS asserts that use of the modular configuration creates a safety "net" in case of any unexpected scenario and provides 100% technical feasibility and perfusion safety. Thus, modularity is the ideal technique for use as the "standard" perfusion policy by non-experienced centres, since it applies to every cardiac procedure while reducing the learning curve required for obtaining optimal results with MiECC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Still, the majority of cardiac surgery has to be performed with the use of a cardiopulmonary bypass (CPB) in order to guarantee sufficient perfusion, oxygenation, and decarboxylation of the body. Several technical upgrades have been introduced to improve the safety and efficiency of conventional CPB (cCPB) systems [ 1 , 2 ]. Nevertheless, the introduction of the minimized extracorporeal circulation (MiECC) has gained widespread interest due to its protective effect on myocardial, renal, and neurological functions [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%